Arts, Maps and People: Exploring engaging objects - Barriga Abril, Carlos Xavier (2016)
Through the artistic practice, this research explores the rhythm of an audience’s journey around a mixed reality object. Similarly, theoretical, observational and self¬reported methods have supported the study unfolding the audience’s engagement with artistic maps. Snail’s Place is the designed artwork that uses both, physical and virtual, environments to represent a city far away from Nottingham. Archeological evidence regarding the artist’s hometown was the resource to bring back the complex dynamic of the city; ambiguous criteria was used to inspire new narratives in the spectators. The physical world is a designed aquarium inhabited by coloured snails, they are tracked and projected in a digital map. Regarding the technical solutions, a Computer Vision and Computer Graphics systems were coded to connect the movement of the snails with the virtual world. The digital map’s surface displays a novel design to hide and reveal the map from different viewpoints, enhancing concepts of exploration and discovery, and supporting the journey of the audience. HCI researchers, artists and general public explored the object revealing key details of their experience. Information about their actions, movements and strategies are profiled in fourteen sheets, as well as commented in a critical evaluation; likewise, the spectator's interpretation is studied as an active interaction, thus, audience become creatively co¬creator of the meanings in the artwork. The participants showed several different strategies to approach artistic maps based on their journey and their actions. Thus, the participant trajectory was defined by a set of focused and unfocused movements, preferred and abandoned viewpoints, and expected and unexpected actions. In addition, the spectators’ interpretative engage displayed different levels of comprehension regarding their vision of the environment, the living entities and, consequently, the quality of the spaces. Finally, based on the profiles and critical evaluation the artist reflects on the artistic and HCI rationale to inform the artwork.